2005
DOI: 10.1146/annurev.immunol.23.021704.115707
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of Multiple Sclerosis

Abstract: Multiple sclerosis (MS) develops in young adults with a complex predisposing genetic trait and probably requires an inciting environmental insult such as a viral infection to trigger the disease. The activation of CD4+ autoreactive T cells and their differentiation into a Th1 phenotype are a crucial events in the initial steps, and these cells are probably also important players in the long-term evolution of the disease. Damage of the target tissue, the central nervous system, is, however, most likely mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
1,488
0
25

Year Published

2005
2005
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,035 publications
(1,523 citation statements)
references
References 365 publications
(340 reference statements)
10
1,488
0
25
Order By: Relevance
“…Several lines of evidence support an early role of autoreactive CD4 ϩ CNS myelin-specific T cells (1,2). In addition, there is epitope spreading such that T cell responses are directed against multiple different myelin antigens (5).…”
Section: Ultiple Sclerosis (Ms) Is An Immune-mediated Disorder Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence support an early role of autoreactive CD4 ϩ CNS myelin-specific T cells (1,2). In addition, there is epitope spreading such that T cell responses are directed against multiple different myelin antigens (5).…”
Section: Ultiple Sclerosis (Ms) Is An Immune-mediated Disorder Inmentioning
confidence: 99%
“…which inflammatory cells from the peripheral blood (PB) migrate to the CNS and cause demyelination and subsequent axonal degeneration (1)(2)(3)(4). Several lines of evidence support an early role of autoreactive CD4 ϩ CNS myelin-specific T cells (1,2).…”
Section: Ultiple Sclerosis (Ms) Is An Immune-mediated Disorder Inmentioning
confidence: 99%
“…Generally, the onset of MS occurs between 20 and 40 years of age, although it may occur, albeit with low frequency, in children and older adults. Women are affected approximately twice as often as men (2). criteria for MS diagnosis are currently applied to adult individuals (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…each of these contribute a modest effect; however, MS development may require additional triggers, such as hormonal variables and environmental factors including infectious agents and emotional stress. among the potential genetic host factors, the association between class i and ii human leukocyte antigen (Hla) alleles in the 6p21 chromosome and MS has been extensively investigated (2,(7)(8)(9)(10)(11)(12), and MS familial aggregation has confirmed that the disease has a significant genetic component (13).…”
Section: Introductionmentioning
confidence: 99%
“…il-23 comprises a p19 subunit that associates with the il-12p40 subunit (4), whereas il-12 is a combination of il-12p35 and the same il-12p40 subunit (5). Furthermore, il-23p19 is a molecule structurally related not only to il-6, but also to granulocyte-colony stimulating factor (G-cSF) and the p35 subunit of il-12.…”
Section: Introductionmentioning
confidence: 99%